2022
DOI: 10.3390/cancers14235902
|View full text |Cite
|
Sign up to set email alerts
|

ATR Inhibitors in Platinum-Resistant Ovarian Cancer

Abstract: Platinum-resistant ovarian cancer (PROC) is one of the deadliest types of epithelial ovarian cancer, and it is associated with a poor prognosis as the median overall survival (OS) is less than 12 months. Targeted therapy is a popular emerging treatment method. Several targeted therapies, including those using bevacizumab and poly (ADP-ribose) polymerase inhibitor (PARPi), have been used to treat PROC. Ataxia telangiectasia and RAD3-Related Protein Kinase inhibitors (ATRi) have attracted attention as a promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 147 publications
0
7
0
Order By: Relevance
“…In this study, we observed that the expression of DDUP was strongly associated with CDDP resistance in ovarian cancer and was inversely correlated with the survival rate of patients with ovarian cancer receiving platinum-based chemotherapy. Notably, treatment with an ATR inhibitor abolished DDUP-induced DNA damage repair and protection against apoptosis, leading to the development of CDDP-resistant ovarian cancer cells that were more vulnerable to platinum-based chemotherapeutic agents [ 39 , 40 ]. Altogether, the findings highlight the importance of DDUP as a predictive biomarker of CDDP resistance and possibly represent a potential strategy for the treatment of CDDP-resistant ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that the expression of DDUP was strongly associated with CDDP resistance in ovarian cancer and was inversely correlated with the survival rate of patients with ovarian cancer receiving platinum-based chemotherapy. Notably, treatment with an ATR inhibitor abolished DDUP-induced DNA damage repair and protection against apoptosis, leading to the development of CDDP-resistant ovarian cancer cells that were more vulnerable to platinum-based chemotherapeutic agents [ 39 , 40 ]. Altogether, the findings highlight the importance of DDUP as a predictive biomarker of CDDP resistance and possibly represent a potential strategy for the treatment of CDDP-resistant ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An increased sensitivity to ATRi in HR-deficient cancers in ovarian cancer cell lines has been shown in literature (Krajewska et al, 2015), however, the specific pathway information was not known and could be used to identify biomarkers for patient selection. Next, we compared the resistance mechanism of ATRi to irinotecan and gemcitabine in ovarian cancer to identify potential similarities or differences to these compounds, with irinotecan suggested and gemcitabine being tested as combination therapy with ATRi in platinum-resistant ovarian cancer (Konstantinopoulos et al, 2023;Li et al, 2022). Our results showed a different profile of genes driving resistance to AZD6738 compared to irinotecan in ovarian cancer (Figure 11), whereas its resistance mechanism was similar to that observed in gemcitabine (involving predominantly G1/S cell cycle genes that drive cell cycle progression through E2F transcription and to a lesser extent NER genes).…”
Section: Signaling Pathway Evaluation Of Atr Inhibitors Such As Azd6738mentioning
confidence: 99%
“…The ATR/CHK1 pathway acts as a sensor detecting single-stranded DNA breaks that lead to cell-cycle arrest. Combined ATR and PARP inhibition has been evaluated across multiple studies; despite promising preclinical data, the phase 2 CAPIRI trial failed to demonstrate a clinical benefit in platinum-resistant epithelial ovarian cancer [ 129 , 130 ]. Prexasertib, a CHK1 inhibitor, was also evaluated in BRCA wild-type HGSOC, where the majority (79%) of the patients had platinum-resistant or refractory disease.…”
Section: Overcoming Platinum Resistance In Ovarian Cancermentioning
confidence: 99%